1996
DOI: 10.1007/bf01411265
|View full text |Cite
|
Sign up to set email alerts
|

Experimental hydrocephalus and hydromyelia: A new insight in mechanism of their development

Abstract: One group of cats had an acrylic screw implanted into the adqueduct of Sylvius, while the other group of animals received a solution of kaolin into the cisterna magna. Three weeks later the dye phenolsulphonphthalein was instilled into the lateral ventricle to ascertain communication between CSF compartments, and thereafter the brain was perfused with formalin. As shown by planimetry of brain ventricles both groups of experimental animals developed hydrocephalus, i.e., coronal surface of brain ventricles was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
3
14
0
1
Order By: Relevance
“…This consideration is supported by the observations that in patients with communicative and non-communicative hydrocephalus, transmantle pressure is absent (Stephensen et al, 2002). All of the evidence supports the idea that the transmantle pressure gradient may not be necessary or instrumental for the development of hydrocephalus, and that some other factors such as an increase in the ventricular CSF pulse pressure without affecting the CSF pressure (Di Rocco et al, 1978), an impairment of systolic-diastolic displacement of the CSF with the development of periventricular ischemia (Miše et al 1996), changes in the arterial pulsations (Greitz, 2004 and, an increase in ventricular CSF osmolarity without affecting the CSF pressure (Krishnamuthy et al, 2009), and venous compliance (Bateman, 2000 and2003) may play an important role in the development of that pathological process (see Section 8. -Mechanisms of hydrocephalus development which are not in accordance with the classical hypothesis of CSF hydrodynamics).…”
Section: The Transmantle Pressure Gradientmentioning
confidence: 71%
See 1 more Smart Citation
“…This consideration is supported by the observations that in patients with communicative and non-communicative hydrocephalus, transmantle pressure is absent (Stephensen et al, 2002). All of the evidence supports the idea that the transmantle pressure gradient may not be necessary or instrumental for the development of hydrocephalus, and that some other factors such as an increase in the ventricular CSF pulse pressure without affecting the CSF pressure (Di Rocco et al, 1978), an impairment of systolic-diastolic displacement of the CSF with the development of periventricular ischemia (Miše et al 1996), changes in the arterial pulsations (Greitz, 2004 and, an increase in ventricular CSF osmolarity without affecting the CSF pressure (Krishnamuthy et al, 2009), and venous compliance (Bateman, 2000 and2003) may play an important role in the development of that pathological process (see Section 8. -Mechanisms of hydrocephalus development which are not in accordance with the classical hypothesis of CSF hydrodynamics).…”
Section: The Transmantle Pressure Gradientmentioning
confidence: 71%
“…The increase in systolic pressure in the brain should distend the brain toward the skull and simultaneously compress the periventricular region of the brain against the ventricles, with the final result being the enlargement of the ventricles and the narrowing of the subarachnoid space. The fact that systolic pressure could be involved in the pathogenesis of hydrocephalus was elaborated in experiments on cats (Miše et al 1996) in which the importance of systolic craniospinal displacement was suggested as the reason for the hydrocephalus development.…”
Section: Pulsatility Hypothesesmentioning
confidence: 99%
“…It was shown in cats that 3 weeks after the application of kaolin in the cisterna magna with the obstruction of cervical subarachnoid space, or the stenosis of the aqueduct with a plastic screw, dilatation of ventricles is developed without a rise in the ventricular CSF pressure (Miše et al 1996). The acute experiments show that an occlusion of the aqueduct itself does not cause the rise of CSF pressure in isolated ventricles and their dilatation .…”
Section: Criticism Of the Classic Hypothesis Of Cerebrospinal Fluid Fmentioning
confidence: 99%
“…For example, some other factors, such as an increase in the ventricular CSF pulse pressure (Di Rocco et al, 1978), an impairment of systolic-diastolic displacement of the CSF with the development of periventricular ischemia (Miše et al, 1996), cardiac disease (Luciano and Dombrowski, 2007), changes in arterial pulsations (Greitz, 2004 and and venous compliance (Bateman, 2000 and2003) may play an important role in the development of that pathological process.…”
Section: Criticism Of the Classic Hypothesis Of Cerebrospinal Fluid Fmentioning
confidence: 99%
“…However, a drawback of this surgical approach was the CSF leakage from the subarachnoid space, as the closing of the surgical wound could not be prevented. To prevent the CSF leakage, a different surgical approach to the aqueduct was used in these experiments, as described in detail in our previous paper (Miše et al, 1996). In short, a burr hole (10 mm in diameter) was made in the midline of the occipital bone and the exposed dura was incised.…”
Section: Aqueductal Occlusion and Csf Pressure Measurementmentioning
confidence: 99%